Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America - Wild, Alexander L.; Cuezzo, Fabiana (Zootaxa, 2006)
We describe a new genus, Gracilidris Wild & Cuezzo gen. nov., and a new species, G. pombero Wild and Cuezzo sp. nov., of dolichoderine ants (Hymenoptera: Formicidae: Dolichoderinae) from Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr.